The assimilative capacity of some rivers in the Philippines - Ocampo, Marcial T.
The objective of this thesis is to quantify the organic assimilative capacity of eight rivers in the Meycauayan River System. This was accomplished by obtaining first water quality and stream flow data from NPCC and BPW, respectively. In addition, BOD incubation data from EDF was obtained to complete the data requirements of this study. Regression analysis using the Method of Least Square was used in estimating the deoxygenation constant, sedimentation/adsorption constant, resuspension/runoff rate, and respiration/photosynthesis rate. For the reaeration constant, an equation considering oxygen diffusion, stream turbulence, and river bed geometry was used. Once the oxygen-sag equation parameters are known, the critical distances for maintaining at least 4.0 mg/L and 0.0 mg/L DO were calculated iteratively using the Regula-Falsi Method. For sensitivity analysis, yhis step was repeated using the original model developed by Streeter and Phelps. Finally, the assimilative capacity was estimated from the stream discharge and the chane in BOD concentration. All the calculations were performed in a programable HP-25 Continuous Memory Calculator.
Appendices: leaves 110-150.
Thesis (M.S.)--University of the Philippines, Quezon City.
Typescript.
Keywords: Rivers -- Philippines -- Bulacan; Water quality -- Measurement